Neurological Sciences - Federico, Antonio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Neurological Sciences is intended to provide a medium for the communication of results and ideas in the field of neuroscience. The journal welcomes contributions in both the basic and clinical aspects of the neurosciences. The official language of the journal is English. Reports are published in the form of original articles, short communications, editorials, reviews and letters to the editor. Original articles present the results of experimental or clinical studies in the neurosciences, while short communications are succinct reports permitting the rapid publication of novel results. Original contributions may be submitted for the special sections History of Neurology, Health Care and Neurological Digressions - a forum for cultural topics related to the neurosciences. The journal also publishes correspondence book reviews, meeting reports and announcements. Manuscripts submitted for publication must contain a statement to the effect that all human studies have been reviewed by the appropriate ethics committee and have therefore been performed in accordance with the ethical standards laid down in an appropriate version of the 1965 Declaration of Helsinki. It should also be stated clearly in the text that all persons gave their informed consent prior to their inclusion in the study. Details that might disclose the identity of the subjects under study should be omitted. Reports of animal experiments must state that the Principles of Laboratory Animal Care (NIH publication no. 86-23 revised 1985) were followed as were applicable national laws (e.g. the current version of the German Law on the Protection of Animals). The Editor-in-Chief reserves the right to reject manuscripts that do not comply with the above-mentioned requirements. Authors will be held responsible for false statements or for failure to fulfill such requirements. The journal is open for publication of supplements and for publishing abstracts of scientific meetings. Conditions can be obtained from the Editor-in-Chief or the publisher.
Keywords: Neuroradiology; Neurology; Neurosurgery; Psychiatry; Neurology; Neuroradiology; Neurosurgery; Psychiatry